PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KEUANGAN MELALUI PERILAKU MANAJER ATAS ISU MANAJEMEN LINGKUNGA SEBAGAI VARIABEL INTERVENING - Amelia Krisnadi (Business Accounting Review, 2016)
This study aimed to examine the relationship between the manager attitudes on the issue of environmental management to financial performance. This study also used the intervening variable which of the manager’s attitude on the issue of environmental management to strengthen the relation between leadership style and the financial performance. This study was quantitative research, and the data were obtained through questionnaires. Then the data obtained were processed by using the Smart PLS software. These results indicate there was a positive and significant relationship between leadership style to financial performance, then positive and significant correlation was also found between the leadership style and manager attitudes on the issue of environmental management. It turns out that the manager's attitude on the issue of environmental manjemen had positive and significant influence on the financial perfoemance.